Hubungan Tingkat Kecemasan dengan Nilai Tekanan Darah Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Lumban Toruan, Dearni Kezia; Simatupang, Lenny (Pustaka Galeri Mandiri, 2026)
Kidney failure refers to a decline in kidney function, namely a reduced ability of the body to eliminate metabolic waste products. This condition is irreversible and requires renal replacement therapy such as kidney transplantation or hemodialysis. Hemodialysis is a kidney replacement procedure designed to remove toxins and waste products from the body when the kidneys are no longer able to function properly. This study aims to determine the relationship between anxiety levels and blood pressure values in patients with chronic kidney failure undergoing hemodialysis at Murni Teguh Memorial Hospital.Method: This study was conducted using a quantitative approach with a correlational design employing Spearman’s test. The purpose was to identify the relationship between anxiety levels and blood pressure values in patients with chronic kidney failure undergoing hemodialysis. The analysis showed a significant relationship between anxiety levels and blood pressure values in patients with chronic kidney failure undergoing hemodialysis at Murni Teguh Memorial Hospital, with a p-value = 0.000 (< 0.05). This indicates that the higher the anxiety level, the higher the blood pressure. There is a significant relationship between anxiety levels and blood pressure values in patients with chronic kidney failure undergoing hemodialysis at Murni Teguh Memorial Hospital